Language use as audience design: The dichotomy of language choice in content-based classrooms in a Malaysian university / Kamisah Ariffin, Norzie Diana Baharum & Rahimah Abd Wahab - Ariffin, Kamisah; Baharum, Norzie Diana; Abu Wahab, Rahimah (Universiti Teknologi MARA, Pahang, 2017)
The language policy in UniversitiTeknologi MARA (UiTM) clearly stipulates that English should be used as the medium of instruction in all programmes taught (Surat PekelilingTNC[100-UiTM (TNC(A) 1/1, 7 May 2003). However, it has been observed that such language policy cannot oversimplify the complexities of the actual language use in the (at least) bilingual context of interaction in the classroom. This paper sets to present and discuss the extensive use of both BM and English in the formal classroom setting in Universiti Teknologi MARA despite the stipulated language policy. The data were represented by the discourse of content-based classroom sessions. The findings suggest language choice was highly governed by the social and psychological variables of the speakers. This paper, however, only focuses on speakers’ language choice and use as audience design in the context of interaction. Using Bell’s (1984; 2001) audience design model as a framework, the data indicate that the impact of the audience on the speakers’ speech style depends on how they ratify and accommodate the audience in terms of their norms of interaction, competence, linguistic awareness and accommodation of the audience’s needs. In addition, speakers’ style-shifting in response to topic(s) is also due to the association of topics with the audience. This study contributes to the advancement of knowledge in the sociolinguistic phenomena in real communication, by providing real examples from a situated discourse. The findings have shown that the regulation of the institutional language policy has oversimplified the complexities of the actual language use in a bilingual/multilingual context of interaction.